2013
DOI: 10.1073/pnas.1304529110
|View full text |Cite
|
Sign up to set email alerts
|

TNFSF15 inhibits vasculogenesis by regulating relative levels of membrane-bound and soluble isoforms of VEGF receptor 1

Abstract: Mouse bone marrow-derived Lin − -Sca-1 + endothelial progenitor cell (EPC) has pluripotent abilities such as supporting neovascularization. Vascular endothelial growth factor (VEGF) receptor 1 (VEGFR1) (Flt1) recognizes various VEGF isoforms and is critically implicated in a wide range of physiological and pathological settings, including vasculogenesis. Mouse EPC expresses two isoforms of VEGFR1: mFlt1, which transmits ligand-induced signals; and sFlt1, which acts as a negative regulator by sequestering ligan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
69
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 49 publications
(72 citation statements)
references
References 54 publications
1
69
0
Order By: Relevance
“…Previous studies have reported TL1A to be a negative regulator of proliferation for endothelial cells, resulting in inhibition of vasculogenesis (7,11,12). As DR is a microvascular DM-associated vision disease involving vasculogenesis, the present study investigated the levels of TL1A in the retina of rats with DM by immunohistochemical analysis.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Previous studies have reported TL1A to be a negative regulator of proliferation for endothelial cells, resulting in inhibition of vasculogenesis (7,11,12). As DR is a microvascular DM-associated vision disease involving vasculogenesis, the present study investigated the levels of TL1A in the retina of rats with DM by immunohistochemical analysis.…”
Section: Resultsmentioning
confidence: 99%
“…Additionally, TL1A inhibited ~50% of the neovascularization induced by either FGF2 or VEGF in vivo . A recent study Qi et al (12) determined that TL1A inhibited vasculogenesis by regulating the expression levels of the VEGFR1. They also reported that TL1A inhibited VEGF-driven, EPC-supported vasculogenesis in a murine matrigel implant model (12).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The IL6R␣ splice variant enhances IL-6's activities in the mouse central nervous system, leading to changes in body temperature and locomotor activity (51), while IL6R␣/IL-6 double transgenic mice display increases in hepatic hematopoiesis and hepatocellular hyperplasia (52,53). Spliced IL7R␣ exacerbates experimental autoimmune encephalomyelitis (47), while signal-mediated changes in VEGFR1 splicing alters vasculogenesis in tissue culture models systems (54). Increased serum concentrations of select cytokine receptor splice variants can also be indicative of an underlying pathology.…”
Section: Discussionmentioning
confidence: 99%
“…Vascular endothelial growth factor (VEGF) is a wellknown signal protein that stimulates vasculogenesis and angiogenesis and is a soluble dimeric glycoprotein that serves as a strong endothelial cell-specific mitogen of blood vessels (Choi et al 2014;Qi et al 2013). VEGF mediates various angiogenic cellular responses such as survival, migration, and differentiation via the activation of a series of signaling within endothelial cells and is secreted from cardiomyocytes in response to extracellular stimuli (Tirziu et al 2007;Tsoporis et al 2012).…”
Section: Introductionmentioning
confidence: 99%